Economic Burden and Health Care Access for Patients With Inflammatory Bowel Diseases in China: Web-Based Survey Study - Yu, Qiao; Zhu, Chunpeng; Feng, Shuyi; Xu, Liyi; Hu, Shurong; Chen, Hao; Chen, Hanwen; Yao, Sheng; Wang, Xiaoying; Chen, Yan (JMIR Publications, 2021)
BackgroundThe increasing incidence of inflammatory bowel disease (IBD) has imposed heavy financial burdens for Chinese patients; however, data about their financial status and access to health care are still lacking. This information is important for informing patients with IBD about disease treatment budgets and health care strategies. ObjectiveThe aim of this study was to evaluate the economic status and medical care access of patients with IBD through the China Crohn's & Colitis Foundation web-based platform in China. MethodsOur study was performed in 14 IBD centers in mainland China between 2018 and 2019 through WeChat. Participants were asked to complete a 64-item web-based questionnaire. Data were collected by the Wenjuanxing survey program. We mainly focused on income and insurance status, medical costs, and access to health care providers. Respondents were stratified by income and the associations of income with medical costs and emergency visit times were analyzed. ResultsIn this study, 3000 patients with IBD, that is, 1922 patients with Crohn disease, 973 patients with ulcerative colitis, and 105 patients with undetermined colitis were included. During the last 12 months, the mean (SD) direct and indirect costs for per patient with IBD were approximately US $11,668.68 ($7944.44) and US $74.90 ($253.60) in China. The average reimbursement ratios for most outpatient and inpatient costs were less than 50%. However, the income of 85.5% (2565/3000) of the patients was less than ¥10,000 (US $1445) per month. Approximately 96.5% (2894/3000) of the patients were covered by health insurance, but only 24.7% (741/3000) of the patients had private commercial insurance, which has higher imbursement ratios. Nearly 98.0% (2954/3000) of the patients worried about their financial situation. Thus, 79.7% (2392/3000) of the patients with IBD tried to save money for health care and even delayed their medical treatments. About half of the respondents (1282/3000, 42.7%) had no primary care provider, and 52.2% (1567/3000) of the patients had to visit the emergency room 1-4 times per year for the treatment of their IBD. Multivariate analysis revealed that lower income (P=.001) and higher transportation (P=.004) and accommodation costs (P=.001) were significantly associated with the increased number of emergency visits of the patients. ConclusionsChinese patients with IBD have enormous financial burdens and difficulties in accessing health care, which have increased their financial anxiety and inevitably influenced their disease outcomes. Early purchase of private insurance, thereby increasing the reimbursement ratio for medical expenses, and developing the use of telemedicine would be effective strategies for saving on health care costs.